The Secretary's Role in Receiving Leadership Guests at the Medan Health Facilities Security Center (BPFK) Office - Dina Octavia (LPPM STIE EKA PRASETYA, 2023)
The aim of this research is to find out the role of the secretary in receiving leadership guests at the Medan Health Facilities Security Center (BPFK) Office. The techniques used by researchers are the observation method (Observation), the interview method (Interview), the library method (Library Research). In general, guests who come to the Health Facilities Security Hall are official guests from hospitals to take care of medical equipment or medical equipment certificates. Therefore, the role of the secretary is very important in receiving guests before meeting with the leadership. The results of the research are that the secretary plays an important role in helping the management's tasks run smoothly. If the secretary is not there then the work will be hampered in terms of energy, thought and time resulting in reduced work efficiency.